The Improvement Clay Body Formulation For Traditional Lapohan Pottery At Pulau Selakan - Ayob, Norhayati (2021)
This thesis studies about Lapohan pottery which is a traditional pottery of early prehistoric technology that has existed for 3000 years ago in Gua Tengkorak, Semporna. The research problem is focused on studying the level of ability of clay in Pulau Selakan to produce Lapohan to overcome the problem of cracking during the pottery making process.